2010
DOI: 10.1016/j.ultrasmedbio.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Initial Investigation of Acoustic Droplet Vaporization for Occlusion in Canine Kidney

Abstract: Acoustic droplet vaporization (ADV) shows promise for spatially and temporally targeted tissue occlusion. In this study, substantial tissue occlusion was achieved in operatively exposed and transcutaneous canine kidneys by generating ADV gas bubbles in the renal arteries or segmental arteries. Fifteen canines were anesthetized, among which 10 underwent laparotomy to externalize the left kidney and 5 were undisturbed for transcutaneous ADV. The microbubbles were generated by phase conversion of perfluoropentane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 30 publications
7
118
0
1
Order By: Relevance
“…From then award, ADV has been profoundly investigated in the group works of Michigan University with albumin coated perfluoropentane (PFP) nanoparticles, which illustrated substantially applications PFC nanoparticles with ADV in terms of drug delivery, thrombolysis, and gas embolism, etc. [33][34][35][36][37][38][39][40][41][42][43]. Table 1 lists some parameters of candidate perfluorocarbons.…”
Section: The Machanism Of Vaporization In Pfc Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…From then award, ADV has been profoundly investigated in the group works of Michigan University with albumin coated perfluoropentane (PFP) nanoparticles, which illustrated substantially applications PFC nanoparticles with ADV in terms of drug delivery, thrombolysis, and gas embolism, etc. [33][34][35][36][37][38][39][40][41][42][43]. Table 1 lists some parameters of candidate perfluorocarbons.…”
Section: The Machanism Of Vaporization In Pfc Nanoparticlesmentioning
confidence: 99%
“…Currently, PFC nanoparticles show promise for effectively targeted tissue occlusion [38,134]. In Zhang et al's study, substantial localized tissue occlusion was achieved in canine kidneys by gas bubbles in the renal arteries or segmental arteries, which were generated by phase-transition PFC droplets encapsulated in lipid shells or albumin in the blood [38].…”
Section: Vascular Occlusionmentioning
confidence: 99%
See 1 more Smart Citation
“…If these huge microbubbles circulate in the blood, there is an increase in the risk of vascular and pulmonary embolism. 25,26 Microbubbles used clinically are no more than 10 ”m to avoid the risk of embolism. Due to these issues, the safety of HIFU synergists requires further study.…”
mentioning
confidence: 99%
“…In addition, vaporized droplets form highly echogenic vapor bubbles resonant to standard diagnostic ultrasound frequencies which allows for monitored drug delivery and tumor imaging. Moreover, the vaporization of microdroplets is of interest for embolotherapy applications 171,190 . Recently, Shpak et al 175 showed that the vaporization of droplets with ultrasound frequencies in the MHz range is induced by the focusing of superharmonic waves, generated by nonlinear propagation of the ultrasound, with wavelengths of the order of the droplet size.…”
Section: Introductionmentioning
confidence: 99%